A survey on the effect of oral vitamin C supplementation in patients undergoing coronary artery bypass graft surgery - Karbasi, Golaleh; Rahimi, Foad; Shirmohammadi, Mousa; Yarahmadi, Saadi (Chronic Diseases Journal, 2020)
BACKGROUND: The positive effects of antioxidants in preventing atrial fibrillation (AF) after cardiac surgery and their low side effects have been proven. The aim of this study was to evaluate the effect of oral vitamin C supplementation on preventing post-operative AF in patients undergoing coronary artery bypass graft (CABG) surgery. Vitamin C was given orally to the patients three days before surgery for up to 5 days after surgery. This time difference was based on previous studies and cardiologist’s order. METHODS: In this study, patients who underwent CABG surgery, were divided into two groups. The first group (30 patients), as the intervention group, received oral vitamin C supplementation, and the second group (30 patients), as the control group, did not receive vitamin C supplementation. All patients, during the post-operative period, underwent cardiac monitoring in cardiac intensive care unit (CICU). The inclusion criteria were: being over 50 years old, undergoing cardiac surgery only and no other kinds of surgery, undergoing coronary artery bypass surgery for the first time, and no cardio-respiratory arrest during or after surgery. Data were collected by convenience sampling method and were analyzed using SPSS software. RESULTS: The results of this study showed that 7 patients in the control group experienced post-operative AF, while 3 patients in intervention group had the same experience. According to the results, the risk of AF in the intervention and control group was, respectively, 10.0% and 23.3%. Vitamin C significantly decreased the risk of AF after CABG surgery by 2 times. CONCLUSION: According to the results, oral vitamin C supplementation affected the incidence of AF after CABG surgery. Therefore, oral intake of vitamin C supplementation before and after surgery reduces the incidence of AF.